Integrating Potential and Local Wisdom into Digital Biology Learning: A Study on E-Module Efficacy for Enhancing Students' Critical Thinking - Siti Sriyati; Sunarto Sura; Angela Lembang (Universitas Negeri Semarang, 2026)
Students' low critical thinking skills remain a global educational challenge, often attributed to conventional pedagogy and the lack of contextualized learning resources. This study aims to evaluate a biology e-module integrating the local potential and local wisdom of the Toraja Tribe to improve students' critical thinking skills. A pretest-posttest quasi-experimental design was used to compare a control group (using a commonly used biology textbook) and an experimental group (using an e-module on the local wisdom of Toraja). This study involved 140 grade 10 students. Data were collected using a test instrument based on the Ennis framework, and a statistical test was performed using the Mann-Whitney U test. The results showed that implementing the e-module on biodiversity significantly increased students' critical thinking skills (Sig = 0.000 < 0.05) with a large effect size (1.61), confirming the strong impact of context-based digital learning on cognitive development. Research results show that using e-modules on biodiversity significantly improves students' critical thinking skills (Sig = 0.000 < 0.05) with a large effect size (1.61), confirming the strong impact of context-based digital learning on critical thinking skills. Research results show that using e-modules on biodiversity significantly improves students' critical thinking skills (Sig = 0.000 < 0.05) with a large effect size (1.61), confirming the strong impact of context-based digital learning on critical thinking skills. These findings suggest that digitizing local potential and local wisdom is effective in bridging the gap between abstract scientific concepts and students' socio-cultural reality, thereby boosting critical thinking skills.